2006
DOI: 10.1093/alcalc/agl073
|View full text |Cite
|
Sign up to set email alerts
|

Social Inequalities in Alcohol Consumption and Alcohol-Related Problems in the Study Countries of the Eu Concerted Action ‘Gender, Culture and Alcohol Problems: A Multi-National Study’

Abstract: Patterns in the distribution of social inequalities are not universal. Social inequalities in alcohol use differ by gender according to alcohol measure used and differ also across groups of countries. These variations should be taken into account when formulating international and cross-cultural alcohol policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

46
180
5
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(241 citation statements)
references
References 25 publications
46
180
5
10
Order By: Relevance
“…In most of the 15 countries studied, binge drinking was associated with low schooling level, but in the Latin American countries, this consumption was greater among those with higher scholarity. 23 The results of the present study are consistent with these observations. The prevalence of binge drinking was greater among the residents of the metropolitan region and, of these, with higher schooling level.…”
Section: Discussionsupporting
confidence: 92%
“…In most of the 15 countries studied, binge drinking was associated with low schooling level, but in the Latin American countries, this consumption was greater among those with higher scholarity. 23 The results of the present study are consistent with these observations. The prevalence of binge drinking was greater among the residents of the metropolitan region and, of these, with higher schooling level.…”
Section: Discussionsupporting
confidence: 92%
“…Además, estos patrones varían entre hombres y mujeres. Según un estudio llevado a cabo en 15 países por Bloomfield et al 25 , en Alemania, Holanda, Francia, Suiza, y Austria las mujeres con un elevado nivel educativo consumen más alcohol mientras que los hombres con menor nivel de estudios tienen mayor probabilidad de ser bebedores de riesgo. En mujeres no observaron diferencias respecto al binge drinking mientras que en hombres había un gradiente social de mayor riesgo en los de menor nivel educativo.…”
Section: Discussionunclassified
“…3 Numerous studies have shown that women drink smaller quantities, drink less often, and get intoxicated on fewer occasions. [4][5][6] While the hypothesis of a convergence between drinking patterns of men and women has been debated over time, this hypothesis has found limited support. 4,7,8 In another way, gender differences in drinking go beyond drinking patterns.…”
mentioning
confidence: 99%